Critical thinking skills: Profile and mastering concepts of undergraduate students - Herawati Susilo; Umie Lestari; Abdul Gofur; Rizkia Suciati (Institute of Advanced Engineering and Science, 2022)
As one of the 21st-century skills, critical thinking (CT) is required for working in an interdisciplinary setting. Educators are expected to provide learning activities that enhance students’ CT skills. Biology, particularly Cell Biology, is seen as challenging since the topics covered therein relate to those covered in the following semester. This research was conducted out as a preliminary study to improve the quality of the learning process, especially in the Cell Biology course. It aimed to identify students’ CT skills in mastering concepts about Cell Membranes. This study enlisted the participation of 105 students from two universities. This research used an instrument test essay using the rubric CT skills. The findings revealed that undergraduate students’ CT skills were classified as basic in mastering the concept of Cell Membrane.